Implications of China’s Rise for Russia in the Context of East-West Tensions: A Partner in an Anti-Western Agenda or a Threat for Moscow’s Regional Influence? - Toni Michel (Сравнительная политика)
This article examines the widely held presumption that in the light of the recent uptick in tension between Russia and the West, a Russian-Chinese alliance has emerged to challenge the United States and its allies. The essay will inquire whether Beijing can truly be regarded as a Russian ally or whether China’s rise rather represents a threat to vested Russian interests. Analysis of Sino-Russian policy on a global level will be followed by an examination of their interplay on a more regional level, particularly in Central Asia.